Right heart imaging in patients with heart failure: a tale of two ventricles. (September 2016) - Amsallem, Myriam; Kuznetsova, Tatiana; Hanneman, Kate; Denault, Andre; Haddad, François
Abstract : Supplemental Digital Content is available in the text Abstract : Purpose of review: The purpose is to describe the recent advances made in imaging of the right heart, including deformation imaging, tissue, and flow characterization by MRI, and molecular imaging. Recent findings: Recent developments have been made in the field of deformation imaging of the right heart, which may improve risk stratification of patients with heart failure and pulmonary hypertension. In addition, more attention has been given to load adaptability metrics of the right heart; these simplified indices, however, still face challenges from a conceptual point of view. The emergence of novel MRI sequences, such as native T1 mapping, allows better detection and quantification of myocardial fibrosis and could allow better prediction of postsurgical recovery of the right heart. Other advances in MRI include four-dimensional flow imaging, which may be particularly useful in congenital heart disease or for the detection of early stages of pulmonary vascular disease. Summary: The review will place the recent developments in right heart imaging in the context of clinical care and research.